Investigating the role of culture conditions on hypertrophic differentiation in human cartilage endplate cells. Issue 6 (23rd April 2020) - Lakstins, Katherine; Yeater, Taylor; Arnold, Lauren; Khan, Safdar; Hoyland, Judith A.; Purmessur, Devina
Abstract: Cartilage endplate degeneration/calcification has been linked to the onset and progression of intervertebral disc degeneration and there is a critical need to understand mechanisms, such as hypertrophic differentiation, of cartilage endplate degeneration/calcification to inform treatment strategies for discogenic back pain. In vitro cell culture conditions capable of inducing hypertrophic differentiation are used to study pathophysiological mechanisms in articular chondrocytes, but culture conditions capable of inducing a hypertrophic cartilage endplate cell phenotype have yet to be explored. The goal of this study was to investigate the role of culture conditions capable of inducing hypertrophic differentiation in articular chondrocytes on hypertrophic differentiation in human cartilage endplate cells. Isolated human cartilage endplate cells were cultured as pellets for 21 days at either 5% O2 (physiologic for cartilage) or 20.7% O2 (hyperoxic) and treated with 10% fetal bovine serum or Wnt agonist, two stimuli used to induce hypertrophic differentiation in articular chondrocytes. Cartilage endplate cells did not exhibit a hypertrophic cell morphology in response to fetal bovine serum or Wnt agonist but did display other hallmarks of chondrocyte hypertrophy and degeneration such as hypertrophic gene and protein expression, and a decrease in healthy proteoglycans and an increase in fibrous collagen accumulation. These findings demonstrate that cartilage endplate cells take on a degenerative phenotype in response to hypertrophic stimuli in vitro, but do not undergo classical changes in morphology associated with hypertrophic differentiation regardless of oxygen levels, highlighting potential differences in the response of cartilage endplate cells versus articular chondrocytes to the same stimuli.